Influence of Colchicine Concentrations on Wheat Seeds Germination and Seedling Quality - Allafe, Mona. A.; Adam, Asmaa R. (Diyala Agricultural Sciences Journal, 2022)
The study investigated the effect of colchicine (C) on seeds germination, as well as morph physiological traits of wheat, where dry wheat seeds were treated with colchicine at concentrations of (C) were (0.02, 0.04, 0.06, and 0.08 %) compared to soaking in distilled water (control). The variance analysis results of laboratory germination experiments as well as in field experiments under rain-fed conditions showed that there were significant differences (P < 0.05) in the mean of most of the studied quantitative traits: germination quality such as germination force (%), germination energy (%), and laboratory germination (%). Leaf area (cm2), root spread, stem diameter (cm), as well as wet and dry weight under the influence of the different concentrations of colchicine. Where the results showed that when used wheat seeds which pre-soaked with colchicine solution at a concentration of (0.06) % for 56 hours pre-sowing, led to an obvious significant increase in all studied traits morph physiological properties and seedling vigor when compared to the control (untreated seeds - treated with distilled water only) as well as when compared with other concentrations of colchicine.